Galactose enhances oxidative metabolism and reveals mitochondrial dysfunction in human primary muscle cells. - Céline Aguer; Daniela Gambarotta; Ryan J Mailloux; Cynthia Moffat; Robert Dent; Ruth McPherson; Mary-Ellen Harper (PLoS ONE, 2011)
Human primary myotubes are highly glycolytic when cultured in high glucose medium rendering it difficult to study mitochondrial dysfunction. Galactose is known to enhance mitochondrial metabolism and could be an excellent model to study mitochondrial dysfunction in human primary myotubes. The aim of the present study was to 1) characterize the effect of differentiating healthy human myoblasts in galactose on oxidative metabolism and 2) determine whether galactose can pinpoint a mitochondrial malfunction in post-diabetic myotubes.Oxygen consumption rate (OCR), lactate levels, mitochondrial content, citrate synthase and cytochrome C oxidase activities, and AMPK phosphorylation were determined in healthy myotubes differentiated in different sources/concentrations of carbohydrates: 25 mM glucose (high glucose (HG)), 5 mM glucose (low glucose (LG)) or 10 mM galactose (GAL). Effect of carbohydrates on OCR was also determined in myotubes derived from post-diabetic patients and matched obese non-diabetic subjects. OCR was significantly increased whereas anaerobic glycolysis was significantly decreased in GAL myotubes compared to LG or HG myotubes. This increased OCR in GAL myotubes occurred in conjunction with increased cytochrome C oxidase activity and expression, as well as increased AMPK phosphorylation. OCR of post-diabetic myotubes was not different than that of obese non-diabetic myotubes when differentiated in LG or HG. However, whereas GAL increased OCR in obese non-diabetic myotubes, it did not affect OCR in post-diabetic myotubes, leading to a significant difference in OCR between groups. The lack of an increase in OCR in post-diabetic myotubes differentiated in GAL was in relation with unaltered cytochrome C oxidase activity levels or AMPK phosphorylation.Our results indicate that differentiating human primary myoblasts in GAL enhances aerobic metabolism. Because this cell culture model elicited an abnormal response in cells from post-diabetic patients, it may be useful in further studies of the molecular mechanisms of mitochondrial dysfunction.